Analysis of the strategy for selecting Value Added Tax (VAT) overpayment refund mechanism in a coal trading company - Arifa Febriani; Rosyani Muthya (WIM Solusi Prima, 2026)
The selection of a Value Added Tax (VAT) overpayment refund mechanism is a decision that affects a company's cash flow and tax risk. PT X, a coal trading company, consistently experienced VAT overpayments due to the characteristics of its business transactions. Therefore, an appropriate strategy is required to determine the most suitable refund mechanism. This study aims to analyze the factors considered in selecting a VAT overpayment refund mechanism, identify the challenges encountered during the refund process, and examine the strategies implemented to address these challenges while minimizing the risk of tax corrections. This study employed a descriptive qualitative method with a case study approach. Primary and secondary data were collected through interviews with tax consultants and an academic expert, as well as observations and documentation. The data were analyzed based on the applicable tax regulations concerning the implementation of the VAT overpayment refund mechanism at PT X for the 2024 Fiscal Year. The findings indicate that the selection of the refund mechanism is influenced by transaction characteristics, cash flow conditions, the amount of VAT overpayment, the company's level of tax compliance, the risk of tax corrections, and regulatory changes. PT X implemented a combination of the advance refund and tax audit-based refund mechanisms to accelerate cash recovery while optimizing its entitlement to VAT overpayments. This strategy was supported by sound tax administrative practices, thereby improving the effectiveness of the VAT overpayment refund process while minimizing the potential for tax corrections.